ANALYSIS OF EGRA (EXPERIENCE, GENERALIZATION, REINFORCEMENT, APPLICATION) METHOD IN TEACHING PROCESS OF RECOUNT TEXT WRITING ABILITY AT SMPN 7 PALANGKA RAYA - Hasanah, Nunur; Perdana, Indra; Arina Luardini, Maria (Program Studi Magister Pendidikan Bahasa Inggris, Program Pascasarjana, Universitas Palangka Raya, 2023)
This study investigates the teaching process using the EGRA (Experience, Generalization, Reinforcement, Application) method for writing a recount text in the eighth grade at SMPN7 Palangka Raya. It specifically focuses on how the method is utilized in lessons, its presence in teaching plans, and the responses it receives from teachers and students. The EGRA method is selected due to its focus on experiential learning, thereby providing students with opportunities for creativity in their writing and facilitating discussions about their work. Each EGRA stage has its specific objectives, aiding students in understanding, formulating, revising, and applying ideas. Data, collected through observations, interviews, and document review, reveal how the EGRA method affects student participation and assists in effective material delivery, creating an engaging classroom environment. The method encourages various insightful activities and challenges students, thereby stimulating their knowledge and creativity. The research concludes the influential role of the EGRA method in activating student learning and transforming the teacher's role into a facilitator, breaking away from monotonous classroom conditions.